PENGARUH EDUKASI GIZI MENGGUNAKAN MEDIA BOOKLET TERHADAP ASUPAN NATRIUM DAN KALIUM PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS PASUNDAN KOTA SAMARINDA - Nurba’adiah Nurba’adiah; Sepsina Reski, Arifin Hidayat (CV. Adiba Aisha Amira, 2024)
Introduction: The increase in hypertension is influenced by many factors, including factors that can be changed and factors that cannot be changed. Factors that can be changed include family history, nutritional status, physical activity and diet. Some foods that can trigger an increase in hypertension include sodium intake and potassium intake. One strategy for managing hypertension is by carrying out nutritional counseling activities with the aim of gaining good knowledge. The media chosen was a booklet because it is one of the appropriate tools to suit your needs. Objective: This research is to determine the effect of nutritional education using booklet media on sodium and potassium intake in hypertension sufferers in the Pasundan Community Health Center Working Area, Samarinda City. Method: The type of research is quasi experimental design, with a pretest- posttest research design with control group design. The research subjects were 36 people, consisting of 18 people for the experimental group and 18 people for the control group, who were selected using random sampling techniques. Data collected included age, gender, highest level of education, religion and sodium and potassium intake. The instruments used were 24 hour food recall, food photo books, and booklet media. Data analysis used the Wilcoxon Test. Results: There was a significant difference in sodium and potassium intake before and after being given nutritional education using booklet media with values (p=0.001; p<0.05), (p=0.001; p<0.05). Conclusion: This study shows that there is an effect of nutritional education on sodium and potassium intake before and after providing nutritional education, both in the experimental and control groups.